Preparation method and application of flue gas CO2 trapping adsorbent suitable for circulating fluidized bed

By preparing micromesoporous composite silicon-based materials as carbon dioxide adsorbents, the problem of low carbon dioxide capture efficiency in the circulating fluidized bed is solved, and efficient and stable carbon dioxide adsorption effect is achieved, meeting the high adsorption amount and wear resistance requirements of the circulating fluidized bed.

CN119500080APending Publication Date: 2025-02-25CNOOC GAS & POWER GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652426.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively capture carbon dioxide in a circulating fluidized bed, and conventional solid porous materials cannot meet the high adsorption amount and wear resistance requirements of the circulating fluidized bed.

Method used

Micromesoporous composite silicon-based material is used as carbon dioxide adsorbent, and adsorbents with high adsorption amount and suitable particle size are prepared by mixing nano-scale microporous molecular sieve with solution, pyrolysis treatment and polyethyleneimine loading.

Benefits of technology

It has achieved efficient carbon dioxide capture in the circulating fluidized bed. The adsorption amount of carbon dioxide of the adsorbent can reach more than 3mmol/g. The particle size meets the requirements for the use of the circulating fluidized bed, and has good cycling stability and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005141303490000011
    Figure HDA0005141303490000011
  • Figure HDA0005141303490000012
    Figure HDA0005141303490000012
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a flue gas CO2 trapping adsorbent suitable for a circulating fluidized bed. The preparation method provided by the invention comprises the following operation steps: step 1, preparing a nanoscale microporous molecular sieve; the preparation method comprises the following steps: adding hexadecyl trimethyl ammonium bromide and organic amine into deionized water, and mixing to form a solution; 2, mixing the microporous molecular sieve obtained in the step 1 with a solution, sequentially adding cyclohexanone and tetraethoxysilane, and stirring at 60-90 DEG C to obtain a precipitate; step 3, filtering and drying the precipitate obtained in the step 2, and pyrolyzing at 400-700 DEG C to obtain a micro-mesoporous composite silicon-based material; and 4, further loading polyethyleneimine on the silicon-based material obtained in the step 3 through impregnation. The carbon dioxide adsorption capacity of the adsorbent can reach 3 mmol / g or above; the particle has stable performance and good recycling performance, and the particle size can meet the use of a circulating fluidized bed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of carbon dioxide adsorption capture, and specifically relates to a preparation method and application of a flue gas CO2 capture adsorbent suitable for a circulating fluidized bed. Background Art

[0002] In recent years, various natural problems such as global warming, glacier melting, and sea level rise caused by the greenhouse effect have begun to become more and more numerous. Among them, carbon dioxide is the dominant gas of the greenhouse effect. The main source of carbon dioxide emissions is the combustion of fossil fuels such as coal, oil, and natural gas in industrial production. Although green energy and renewable energy are developing rapidly, there is still a long way to go before they can be widely used. In order to effectively slow down the intensification of the greenhouse effect, it is necessary to develop efficient and economical methods to capture the emitted carbon dioxide.

[0003] At present, the carbon dioxide capture and separation technologies that have been successfully applied mainly include chemical absorption, membrane separation and adsorption. Among them, the alkanolamine compound used in the absorption method is monoethanolamine, which has a fast absorption rate and a relatively mature process. It is widely used in industrial processes such as oil refining and synthetic ammonia. However, the amine compound absorption method has high regeneration energy consumption and serious corrosion to the equipment. The membrane separation method uses the difference in permeability of different gases to a film made of polymer materials to separate gases. The membrane separation method has a simple device, but it is generally difficult to achieve large-scale carbon capture. In comparison, the adsorption method usually has simple equipment, easy operation, low energy consumption, low cost, no corrosion and pollution, and is conducive to large-scale application. Therefore, the use of adsorption technology for carbon dioxide capture has great application prospects, and the key is the development of high-performance adsorbents.

[0004] In the fixed bed adsorption process, the adsorption and regeneration of the adsorbent are both in the same device, and the temperature change process consumes a lot of energy. The circulating fluidized bed adsorption process can effectively reduce energy consumption, but at the same time, the requirements for the adsorbent are different, such as high adsorption capacity, certain wear resistance, and particle size cannot be too large. Therefore, some conventional solid porous materials, such as porous carbon materials, molecular sieves, alumina, silica gel, etc., are difficult to meet the requirements of circulating fluidized bed carbon dioxide adsorption capture. Summary of the invention

[0005] Therefore, based on the problems existing in the prior art, the inventors of the present application have proposed, after long-term research, a new porous adsorbent with higher carbon dioxide adsorption capacity and smaller particle size to meet its application in the circulating fluidized bed adsorption process.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a micro-mesoporous composite carbon dioxide adsorbent, comprising the following steps:

[0007] Step 1: preparing nano-scale microporous molecular sieve material; adding hexadecyltrimethylammonium bromide and organic amine into deionized water, and mixing to form a solution;

[0008] Step 2: Mix the microporous molecular sieve in step 1 with the solution, add cyclohexanone and tetraethyl orthosilicate in sequence, and stir at 60-90° C. to obtain a precipitate;

[0009] Step 3: filtering the precipitate obtained in step 2, drying it, and pyrolyzing it at 400-700° C. to obtain a micro-mesoporous composite silicon-based material;

[0010] Optional step four: further loading polyethyleneimine on the silicon-based material obtained in step three by impregnation.

[0011] In some embodiments, the microporous molecular sieve in step 1 includes but is not limited to ZSM-5, 5A, 13X; the particle size may be less than 100 nm, in particular, for example, 50-100 nm;

[0012] In some embodiments, in step 1, the organic amine is one or more selected from triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine;

[0013] In some embodiments, in step 1, the molar ratio of hexadecyltrimethylammonium bromide, organic amine and deionized water is 3:1:10 to 3:1:15.

[0014] In some embodiments, in step 1, mixing can be performed at 20-40°C, for example, at room temperature.

[0015] In some embodiments, in step 2, the mass ratio of the microporous molecular sieve to the solution is 1:500 to 1:1000.

[0016] In some embodiments, in step 2, the mass ratio of cyclohexanone and tetraethyl orthosilicate to molecular sieve is 30:10:1 to 40:10:1.

[0017] In some embodiments, in step 2, stirring is performed at 70-85°C, for example, 80°C.

[0018] In some embodiments, in step three, the pyrolysis temperature is 500-600°C.

[0019] In some embodiments, in step three, the pyrolysis time is 2 to 4 hours.

[0020] In some embodiments, in step 4, the loading amount of polyethyleneimine is 30%-50%, especially 40%, based on the weight of the silicon-based material.

[0021] In some embodiments, in step 4, polyethyleneimine is loaded into the molecular sieve by an impregnation method, in particular, by dissolving polyethyleneimine in one or more solvents selected from alcohols such as methanol, ethanol, and water, and then impregnating polyethyleneimine in the obtained polyethyleneimine solution, for example, and drying at room temperature, such as 20-40°C.

[0022] The present invention also provides a micro-mesoporous composite carbon dioxide adsorbent prepared according to the above preparation method, which has both micropores and mesopores, and the proportion of the mesopore volume to the total pore volume is not less than 70%.

[0023] The particle size of the micro-mesoporous composite carbon dioxide adsorbent according to the present invention is about 50-200 nm.

[0024] The present invention also provides an application of the micro-mesoporous composite carbon dioxide adsorbent in a circulating fluidized bed flue gas CO2 capture process.

[0025] After the above-mentioned micro-mesoporous composite silicon-based material is loaded with organic amine (such as polyethyleneimine), it can be advantageously used in a circulating fluidized bed flue gas CO2 capture process.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The proportion of mesoporous pore volume of the micro-mesoporous composite silicon-based material to the total pore volume is not less than 50%;

[0028] (2) By utilizing both the chemical adsorption of organic amines in the mesopores and the physical adsorption in the micropores, the carbon dioxide adsorption capacity of the adsorbent can reach more than 3 mmol / g;

[0029] (3) The particle size of the adsorbent can meet the requirements of a circulating fluidized bed;

[0030] (4) The adsorbent has stable performance and good recycling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is the X-ray diffraction pattern of the product of Example 1;

[0032] Figure 2 is a scanning electron microscope image of the product of Example 2;

[0033] Figure 3 is a nitrogen adsorption-desorption curve diagram of the product of Example 4;

[0034] Figure 4 is the isothermal adsorption curve of carbon dioxide at 25° C. for the products of Examples 1, 3, 5, and 6 after loading 40% polyethyleneimine;

[0035] Figure 5is an exemplary circulating fluidized bed carbon capture process diagram;

[0036] Figure 6 These are the test results of cyclic adsorption of the products of Examples 2, 4, 5, and 7 in a circulating fluidized bed. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with embodiments and drawings.

[0038] The following detailed description is merely illustrative in nature and is not intended to limit the present invention and its use. In addition, this article is not limited by any theory described in the above prior art or summary of the invention or the following detailed description or examples. The methods, equipment, reagents and conditions used in the examples are, unless otherwise stated, conventional methods, equipment, reagents and conditions in the art.

[0039] Nitrogen adsorption-desorption test: Using a physical adsorption instrument (Quanta Autosorb-iQ), the sample was first degassed at 300°C for 3 hours. After cooling, the N2 adsorption at 77K was tested, and the specific surface area and pore volume were analyzed using the instrument's built-in software.

[0040] Isothermal adsorption test of carbon dioxide: Using a physical adsorption instrument, the sample was first degassed at 300°C for 3 hours, and after cooling, the adsorbent CO2 adsorption was tested at 25°C;

[0041] Cyclic adsorption test in a circulating fluidized bed: The test was carried out in a small-scale circulating fluidized bed homemade by conventional methods. Before the test, the sample was pretreated at 140°C.

[0042] The molecular sieves used in this application were all purchased from Tianjin Nanhua Catalyst Co., Ltd. and are all typical microporous molecular sieves.

[0043] Embodiment 1: First, prepare nano-scale microporous 13X molecular sieve material with a particle size of about 80nm; add hexadecyltrimethylammonium bromide and tetraethylenepentamine together into deionized water, react at room temperature to form a solution, wherein the molar ratio of hexadecyltrimethylammonium bromide, tetraethylenepentamine and deionized water is 3:1:10; mix the microporous molecular sieve with the above solution, wherein the mass ratio of the molecular sieve to the solution is 1:500; add appropriate amounts of cyclohexanone and tetraethyl orthosilicate in sequence, stir at 80°C to obtain a precipitate, wherein the mass ratio of cyclohexanone and tetraethyl orthosilicate to the molecular sieve is 30:10:1; filter the precipitate, dry it, and pyrolyze it at 500°C for 2 hours to obtain a micro-mesoporous composite silicon-based material.

[0044] Example 2: First, prepare a nano-scale microporous 5A molecular sieve material with a particle size of about 70nm; add hexadecyltrimethylammonium bromide and triethylenetetramine together into deionized water, react at room temperature to form a solution, wherein the molar ratio of hexadecyltrimethylammonium bromide, triethylenetetramine and deionized water is 3:1:15; mix the microporous molecular sieve with the above solution, wherein the mass ratio of the molecular sieve to the solution is 1:1000; add appropriate amounts of cyclohexanone and tetraethyl orthosilicate in sequence, stir at 80°C to obtain a precipitate, wherein the mass ratio of cyclohexanone and tetraethyl orthosilicate to the molecular sieve is 30:10:1; filter the precipitate, dry it, and pyrolyze it at 600°C for 4 hours to obtain a micro-mesoporous composite silicon-based material.

[0045] Example 3: First, prepare a nano-scale microporous 13X molecular sieve material with a particle size of about 90nm; add hexadecyltrimethylammonium bromide and pentaethylenehexamine together into deionized water, react at room temperature to form a solution, wherein the molar ratio of hexadecyltrimethylammonium bromide, pentaethylenehexamine and deionized water is 3:1:10; mix the microporous molecular sieve with the above solution, wherein the mass ratio of the molecular sieve to the solution is 1:500; add appropriate amounts of cyclohexanone and tetraethyl orthosilicate in sequence, stir at 80°C to obtain a precipitate, wherein the mass ratio of cyclohexanone and tetraethyl orthosilicate to the molecular sieve is 30:10:1; filter the precipitate, dry it, and pyrolyze it at 600°C for 2 hours to obtain a micro-mesoporous composite silicon-based material.

[0046] Example 4: First, prepare a nano-scale microporous ZSM-5 molecular sieve material with a particle size of about 80nm; add hexadecyltrimethylammonium bromide and pentaethylenehexamine together into deionized water, react at room temperature to form a solution, wherein the molar ratio of hexadecyltrimethylammonium bromide, pentaethylenehexamine and deionized water is 3:1:12; mix the microporous molecular sieve with the above solution, wherein the mass ratio of the molecular sieve to the solution is 1:600; add appropriate amounts of cyclohexanone and tetraethyl orthosilicate in sequence, stir at 80°C to obtain a precipitate, wherein the mass ratio of cyclohexanone and tetraethyl orthosilicate to the molecular sieve is 30:10:1; filter the precipitate, dry it, and pyrolyze it at 550°C for 3 hours to obtain a micro-mesoporous composite silicon-based material.

[0047] Example 5: First, prepare nano-scale microporous 5A molecular sieve material with a particle size of about 70nm; add hexadecyltrimethylammonium bromide and pentaethylenehexamine together into deionized water, react at room temperature to form a solution, wherein the molar ratio of hexadecyltrimethylammonium bromide, pentaethylenehexamine and deionized water is 3:1:12; mix the microporous molecular sieve with the above solution, wherein the mass ratio of the molecular sieve to the solution is 1:600; add appropriate amounts of cyclohexanone and tetraethyl orthosilicate in sequence, stir at 80°C to obtain a precipitate, wherein the mass ratio of cyclohexanone and tetraethyl orthosilicate to the molecular sieve is 30:10:1; filter the precipitate, dry it, and pyrolyze it at 550°C for 3 hours to obtain a micro-mesoporous composite silicon-based material.

[0048] Example 6: First, prepare a nano-scale microporous 13X molecular sieve material with a particle size of about 90nm; add hexadecyltrimethylammonium bromide and triethylenetetramine together into deionized water, react at room temperature to form a solution, wherein the molar ratio of hexadecyltrimethylammonium bromide, triethylenetetramine and deionized water is 3:1:13; mix the microporous molecular sieve with the above solution, wherein the mass ratio of the molecular sieve to the solution is 1:700; add appropriate amounts of cyclohexanone and tetraethyl orthosilicate in sequence, stir at 80°C to obtain a precipitate, wherein the mass ratio of cyclohexanone and tetraethyl orthosilicate to the molecular sieve is 30:10:1; filter the precipitate, dry it, and pyrolyze it at 550°C for 3 hours to obtain a micro-mesoporous composite silicon-based material.

[0049] Example 7: First, prepare a nano-scale microporous ZSM-5 molecular sieve material with a particle size of about 80nm; add hexadecyltrimethylammonium bromide and triethylenetetramine together into deionized water, react at room temperature to form a solution, wherein the molar ratio of hexadecyltrimethylammonium bromide, triethylenetetramine and deionized water is 3:1:12; mix the microporous molecular sieve with the above solution, wherein the mass ratio of the molecular sieve to the solution is 1:700; add appropriate amounts of cyclohexanone and tetraethyl orthosilicate in sequence, stir at 80°C to obtain a precipitate, wherein the mass ratio of cyclohexanone and tetraethyl orthosilicate to the molecular sieve is 30:10:1; filter the precipitate, dry it, and pyrolyze it at 550°C for 3 hours to obtain a micro-mesoporous composite silicon-based material.

[0050] The silicon-based materials obtained in Examples 1-7 were immersed in an ethanol solution of polyethyleneimine respectively, and then dried to obtain an adsorbent loaded with polyethyleneimine (40%).

[0051] Test Case

[0052] The properties of the porous adsorbent prepared by the present invention are as follows:

[0053] Figure 1It is the X-ray diffraction diagram of the product of Example 1; it can be seen that the characteristic peaks appearing in the diagram are all characteristic peaks of 13X molecular sieve, indicating that the synthesized micro-mesoporous composite material does not destroy the crystalline structure of 13X molecular sieve.

[0054] Figure 2 This is a scanning electron microscope image of the product of Example 2 at 35,000 times magnification; it can be seen from the image that the synthesized adsorbent is composed of fine particles and has a loose pore structure.

[0055] Figure 3 The figure is a nitrogen absorption-desorption curve of the product of Example 4; the upper curve is the desorption curve, and the lower curve is the adsorption curve. It can be seen from the figure that the nitrogen adsorption amount of the prepared adsorbent increases with the increase of relative pressure. By calculating the BET formula, it can be obtained that its specific surface area is 560m 2 / g, total pore volume 0.84m 3 / g, mesopore volume 0.65m 3 / g.

[0056] Figure 4 The isothermal adsorption curves of carbon dioxide at 25° C. for the silicon-based materials of Examples 1, 3, 5, and 6 after loading 40% polyethyleneimine; at 1 atm, the adsorption amounts are all greater than 3 mmol / g.

[0057] Figure 6 The adsorbent obtained by loading 40% polyethyleneimine with the silicon-based materials of Examples 2, 4, 5, and 7 is subjected to cyclic adsorption test in a circulating fluidized bed, and the test conditions are: flue gas composition 95% N2, 5% CO2; adsorption temperature: room temperature; regeneration temperature: 140°C. It can be seen that during the 5 cycles, the CO2 adsorption retention rate of the adsorbent is greater than 90%, indicating that it has good cyclic stability.

[0058] The wear resistance of the micro-mesoporous composite silicon-based materials prepared in Examples 1-7 was tested using a catalyst wear index tester (compliant with HG / T4861-2015), and the results are as follows:

[0059] Table 1 Wear resistance of adsorbent materials

[0060]

[0061] The above tests show that the adsorbent prepared according to the present invention has a high adsorption capacity, a certain wear resistance, and a suitable particle size, and can therefore be effectively used in a circulating fluidized bed to adsorb CO2 therein.

Claims

1. A method for preparing a micro-mesoporous composite carbon dioxide adsorbent, comprising the following steps: Step 1: prepare a nano-scale microporous molecular sieve; add hexadecyltrimethylammonium bromide and an organic amine into deionized water and mix to form a solution; Step 2: Mix the microporous molecular sieve in step 1 with the solution, add cyclohexanone and tetraethyl orthosilicate in sequence, and stir at 60-90° C. to obtain a precipitate; Step 3: filtering the precipitate obtained in step 2, drying it, and pyrolyzing it at 400-700° C. to obtain a micro-mesoporous composite silicon-based material; Optional step four: further loading polyethyleneimine on the silicon-based material obtained in step three by impregnation.

2. The preparation method according to claim 1, wherein In step 1, the microporous molecular sieve includes ZSM-5, 5A, 13X molecular sieve; and / or the particle size of the microporous molecular sieve is less than 100 nm.

3. The preparation method according to claim 1 or 2, wherein In step 1, the organic amine is one or more selected from triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.

4. The preparation method according to any one of claims 1 to 3, wherein In step 1, the molar ratio of hexadecyltrimethylammonium bromide, organic amine and deionized water is 3:1:10 to 3:1:15; and / or, in step 1, the mixing is carried out at 20-40°C.

5. The preparation method according to any one of claims 1 to 4, wherein In step 2, the mass ratio of the microporous molecular sieve to the solution is 1:500 to 1:1000.

6. The preparation method according to any one of claims 1 to 5, wherein In step 2, the mass ratio of cyclohexanone, tetraethyl orthosilicate and molecular sieve is 30:10:1 to 40:10:1; and / or, in step 2, stirring is performed at 70 to 85°C.

7. The preparation method according to any one of claims 1 to 6, wherein In step three, the pyrolysis temperature is 500-600° C.; and / or, in step three, the pyrolysis time is 2-4 hours.

8. The preparation method according to any one of claims 1 to 7, wherein In step 4, based on the weight of the silicon-based material, the loading amount of polyethyleneimine is 30%-50%, especially 40%.

9. The micro-mesoporous composite carbon dioxide adsorbent prepared by the preparation method according to any one of claims 1 to 8, which has both micropores and mesopores, and the proportion of mesopore volume to total pore volume is not less than 70%, especially, its particle size is 50-200nm.

10. Use of the micro-mesoporous composite carbon dioxide adsorbent prepared by the preparation method according to any one of claims 1 to 8, or the micro-mesoporous composite carbon dioxide adsorbent according to claim 9 in a circulating fluidized bed flue gas CO2 capture process.